2013
DOI: 10.1149/2.093309jes
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SOFCs Using Reference Electrodes

Abstract: Reference electrodes are frequently applied to isolate the performance of one electrode in a solid oxide fuel cell. However, reference electrode simulations raise doubt to the veracity of data collected using reference electrodes. The simulations predict that the reported performance for the one electrode will frequently contain performance of both electrodes. Nonetheless, recent reports persistently treat data so collected as ideally isolated. This work confirms the predictions of the reference electrode simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…The changes in the aging behavior can thus be predicted through pairing the defect chemistry model with an appropriate LSM oxygen reduction model. The authors are currently working toward incorporating the changing defect concentrations into an existing LSM oxygen reduction and corresponding SOFC multiphysics model which can predict the electrochemical performance of a porous LSM electrode similar to the one found in the symmetrical cell samples [39][40][41]. By stepping the defect concentrations in time based upon reasonable cation diffusion coefficients, simulated impedance aging data will be created.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the aging behavior can thus be predicted through pairing the defect chemistry model with an appropriate LSM oxygen reduction model. The authors are currently working toward incorporating the changing defect concentrations into an existing LSM oxygen reduction and corresponding SOFC multiphysics model which can predict the electrochemical performance of a porous LSM electrode similar to the one found in the symmetrical cell samples [39][40][41]. By stepping the defect concentrations in time based upon reasonable cation diffusion coefficients, simulated impedance aging data will be created.…”
Section: Discussionmentioning
confidence: 99%
“…With introducing methane, the R ct increased by 3e4 orders in magnitude, which indicated that the active sites of Ni catalyst was diminished by carbon species deposition on the surface of Ni [192]. From the EIS and CV analysis, the exchange current densities for hydrogen oxidation at GTE Ni-YSZ/YSZ anodes were found to be increased exponentially from ca.…”
Section: Figure 529mentioning
confidence: 99%
“…The contact of silver with an electrolyte may temporarily increase the cell performance because of increase in the three-phase boundary, but the silver deposits may short-circuit the cell. Deposition of silver increased the risk of silver penetration into pinholes in the electrolyte and consequently short-circuit formation [36]. The silver migration was noticed only for the part of the cell near the cell inlet.…”
Section: Cathode Conductive Layermentioning
confidence: 99%